The translatics of translation - Asruddin Barori Tau (Journal of Modern Languages, 2017)
The project on which this paper is based offers Translatics as a theory of translation which is designed and developed as an alternative that challenges the mainstream views currently held within translation studies. To familiarize the readers with Translatics, an attempt will be made to provide and describe its foundational key concepts and features particularly in contrast with the concepts and features that are characteristic of the mainstream transfer/equivalence-based and hermeneutics-based theories of translation. In particular, one concept of critical importance that will be described that fundamentally distinguishes Translatics from the mainstream perspectives is concerned with its defined notion of translation as translational semiottic communication (TSC) and in its turn as metasemiotic. Being SFL-inspired, the defined translation as TSC and in turn as metasemiotic is an abstract semiotic concept which is more abstract than Martin's Hjemslevian connotative semiotic. The aim of this paper is twofold: to introduce Translatics as a new way of meaning and at the same time to contribute to the broadening of the academic horizons of readers who are interested in translation studies as a transdisciplinary study of translational semiotic phenomena.